Mechanical activation of angiotensin II type 1 receptors causes actin remodelling and myogenic responsiveness in skeletal muscle arterioles. (13th October 2016) - Hong, Kwangseok; Zhao, Guiling; Hong, Zhongkui; Sun, Zhe; Yang, Yan; Clifford, Philip S.; Davis, Michael J.; Meininger, Gerald A.; Hill, Michael A.
Abstract : Key points: Candesartan, an inverse agonist of the type 1 angiotensin II receptor (AT1 R), causes a concentration‐dependent inhibition of pressure‐dependent myogenic tone consistent with previous reports of mechanosensitivity of this G protein‐coupled receptor. Mechanoactivation of the AT1 R occurs independently of local angiotensin II production and the type 2 angiotensin receptor. Mechanoactivation of the AT1 R stimulates actin polymerization by a protein kinase C‐dependent mechanism, but independently of a change in intracellular Ca 2+ . Using atomic force microscopy, changes in single vascular smooth muscle cell cortical actin are observed to remodel following mechanoactivation of the AT1 R. Abstract: The Gq/11 protein‐coupled angiotensin II type 1 receptor (AT1 R) has been shown to be activated by mechanical stimuli. In the vascular system, evidence supports the AT1 R being a mechanosensor that contributes to arteriolar myogenic constriction. The aim of this study was to determine if AT1 R mechanoactivation affects myogenic constriction in skeletal muscle arterioles and to determine underlying cellular mechanisms. Using pressure myography to study rat isolated first‐order cremaster muscle arterioles the AT1 R inhibitor candesartan (10 −7 –10 −5 m ) showed partial but concentration‐dependent inhibition of myogenic reactivity. Inhibition was demonstrated by a rightward shift in the pressure–diameter relationship over the intraluminal pressure range, 30–110 mmHg. Pressure‐induced changes in global vascular smooth muscle intracellular Ca 2+ (using Fura‐2) were similar in the absence or presence of candesartan, indicating that AT1 R‐mediated myogenic constriction relies on Ca 2+ ‐independent downstream signalling. The diacylglycerol analogue 1‐oleoyl‐2‐acetyl‐sn‐glycerol (OAG) reversed the inhibitory effect of candesartan, while this rescue effect was prevented by the protein kinase C (PKC) inhibitor GF 109203X. Both candesartan and PKC inhibition caused increased G‐actin levels, as determined by Western blotting of vessel lysates, supporting involvement of cytoskeletal remodelling. At the single vascular smooth muscle cell level, atomic force microscopy showed that cell swelling (stretch) with hypotonic buffer also caused thickening of cortical actin fibres and this was blocked by candesartan. Collectively, the present studies support growing evidence for novel modes of activation of the AT1 R in arterioles and suggest that mechanically activated AT1 R generates diacylglycerol, which in turn activates PKC which induces the actin cytoskeleton reorganization that is required for pressure‐induced vasoconstriction. Key points: Candesartan, an inverse agonist of the type 1 angiotensin II receptor (AT1 R), causes a concentration‐dependent inhibition of pressure‐dependent myogenic tone consistent with previous reports of mechanosensitivity of this G protein‐coupled receptor. Mechanoactivation of the AT1 R occurs independently of local angiotensin II production and the type 2 angiotensin receptor. Mechanoactivation of the AT1 R stimulates actin polymerization by a protein kinase C‐dependent mechanism, but independently of a change in intracellular Ca 2+ . Using atomic force microscopy, changes in single vascular smooth muscle cell cortical actin are observed to remodel following mechanoactivation of the AT1 R.